2020
DOI: 10.26717/bjstr.2020.30.004980
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Tumours in Dogs and its Treatment Option- A Review

Abstract: Mammary tumors are the most common type of tumors in intact female dogs. Several epidemiologic studies have been conducted over the years and provide an estimate of the incidence of canine mammary gland tumors. This type of treatment recommendation may also be made in dogs based on recognized, well-accepted prognostic factors such as tumor size, stage, type, and histologic differentiation. Based on the limited clinical information available in veterinary medicine, the drugs that are effective in human breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The decisional process of the clinician should start with a complete evaluation of the patient, in order to assess its suitability for mastectomy and to decide the appropriate surgical technique and whether to include gonadectomy in its surgical plan. Patients presenting with mammary tumors should be carefully checked for evidence of metastatic disease 30 , starting with the evaluation of regional lymph nodes. These organs are difficult to assess when normal, and the easily palpable ones should be checked, possibly indicating regional metastasis 1,31 , to be confirmed through cytological examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decisional process of the clinician should start with a complete evaluation of the patient, in order to assess its suitability for mastectomy and to decide the appropriate surgical technique and whether to include gonadectomy in its surgical plan. Patients presenting with mammary tumors should be carefully checked for evidence of metastatic disease 30 , starting with the evaluation of regional lymph nodes. These organs are difficult to assess when normal, and the easily palpable ones should be checked, possibly indicating regional metastasis 1,31 , to be confirmed through cytological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Although in our study, we could not evaluate the effect of previous pregnancies or pseudo-pregnancies due to the lack of data, future research should investigate these as potential factors influencing the development of mammary tumours. Patients presenting with mammary tumours should be carefully checked for evidence of metastatic disease, 30 starting with the evaluation of regional lymph nodes. These organs are difficult to assess when normal, and the easily palpable ones should be checked, possibly indicating regional metastasis, 1,31 to be confirmed through cytological examination.…”
Section: Discussionmentioning
confidence: 99%
“…A genome-wide association study (GWAS) is a useful tool for understanding genetic and phenotypic variation. However, its usefulness is dependent on the level of linkage disequilibrium (LD) as only a limited number of markers can be genotyped ( 9 , 10 ). In one study, canine LD was found to be 20–50 times more extensive than that in humans, indicating that fewer SNPs are required for genotype analysis in dogs than in humans ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are limited studies of genetic mutations involved in the development of canine MGTs. In one study, one single-nucleotide polymorphism (SNP) in the BRCA1/2 genes, in which mutations are known to be associated with an 84% increased risk of breast cancer in human medicine, was confirmed to be significantly associated with canine MGTs ( 1 , 9 ). In another study, the significance of 10 genes associated with human breast cancer was analyzed in dogs with MGT ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The tumor incidence rate increases rapidly in animals from approximately six years of age. The average age of dogs with mammary gland tumors is 10 to 11 years (Fesseha, 2020;Valdivia et al, 2021). Treatment of mammary gland tumors is through the surgical approach of mastectomy namely removal of mammary gland tumors.…”
Section: Introductionmentioning
confidence: 99%